THE CORRELATION BETWEEN STUDENT’S READING STRATEGY AND READING COMPREHENSION OF SECONDARY SCHOOL - Ika Nur Aini; Suvi Akhiriyah (Faculty of Teacher Training and Education, Universitas Sriwijaya, 2022)
Reading strategies are procedures to assist students’ reading comprehension which play an active role in reading literacy. This quantitative study aims to find out the reading strategies mostly used by students and to find out the correlation between students' reading strategies and their reading comprehension. The research design used was correlational study. The total sample in this study was 74 ninth graders in one of junior high schools in Surabaya. The participants were chosen using the convenience sampling method due to the availability of the students. The data were collected by using Survey of Reading Strategies (SORS) questionnaire and reading comprehension test. The data were analyzed by using descriptive statistics to find out the strategy mostly used by students, and Pearson Product Moment to find out the correlation between variables. The results showed that the students often used Problem-Solving Strategy (M= 4), Global Reading Strategy (M= 3.04), and Support Reading Strategy (3.04). Furthermore, it was found that there was no correlation between the two variables (p-value= 0.790, >0.05). According to the result, good reading strategy does not affect the reading comprehension correlation.